ISDEV TO STUDY ON OFFERING EXPERTISE IN VIETNAM - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 28 March 2016 The Centre for Islamic Development Management Studies (ISDEV) at Universiti Sains Malaysia (USM) would be conducting research work on ‘Leadership in Islamic Service Management’ in Vietnam beginning 28 May 2016.